International interests: Student and industry perspectives on agicultural communications curriculum development in Ontario - Madison Dyment; Annie Specht; Emily Buck (Advancements in Agricultural Development)
This study explores the potential development of an agricultural communications program at the [Institution]. It aims to understand the current knowledge of and interest in the discipline among Ontarian agriculture students and industry professionals, and the perceived importance and employability of hypothetical program graduates, contributing to the Sustainable Development Goal of quality education. Using a qualitative descriptive case study approach, focus groups with 18 students and six industry professionals were conducted. Data were collected through open-ended questions, analyzed using open coding and thematic analysis, and triangulated with demographic surveys. The findings reveal a general lack of understanding of agricultural communications among Ontarian students, who nonetheless recognize the field's potential to bridge gaps between producers and consumers, particularly through social media and diverse job opportunities. Industry professionals emphasized the growing importance of storytelling, crisis communication, and the need for poly-skilled graduates capable of addressing varied communication needs within the agricultural sector. Both stakeholder groups expressed interest in an agricultural communications academic program. Recommendations include engaging broader industry support for the program, integrating agricultural communications training across existing agricultural disciplines at the [Institution], and continuing research to refine curriculum development.